Asynchrony between in vivo and in vitro rabbit embryos - García, María-Luz; Belabbas, Rafik; Muelas, Raquel; Agea, Iván; Argente, María-José (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Comparative features of embryos developed under in vitro and in vivo conditions are particularly important in designing embryo transfer procedures that fulfil embryo-recipient synchronization requirements. Objective: To determine the degree of asynchrony in rabbit embryo development between cultured and in vivo embryos. Methods: A total of 55 non-lactating multiparous female rabbits were used. Embryos were classified as 16-cells or early morulae at 48 hours post-coitum (hpc). Embryos were cultured during 30 or 32 h and embryo development was compared with in vivo embryos of 72 hpc. In vitro and in vivo embryos at 72 hpc were classified as early or compacted morulae. Bayesian statistics was used. Difference between in vivo and in vitro embryos and the actual probability of the difference between the in vivo and in vitro embryo higher than zero (P) was estimated. Results: The percentage of compacted morulae was higher in in vivo embryos than in in vitro embryos with +6 h of asynchrony (73.5 and 32.8%, P=1.00). But the percentage of compacted morulae was similar with +8 h asynchrony. Conclusions: In vitro embryos delay their development by + 8 hours compared to in vivo embryos.